AUGMENTED REALITY IN E-COMMERCE: - Kembau, Agung Stefanus; Laimeheriwa, Imagodeo Bideyesa; Kumaat, Arief Perdana (Universitas Nusa Cendana, 2025)
In the rapidly evolving world of e-commerce, Augmented Reality (AR) stands out as a transformative force, shaping consumer behavior and decision-making. This study delves into the profound impact of AR on digital behavioral intentions, particularly focusing on how interactivity, mental image, and consumer attitudes intertwine to drive these intentions. By surveying 120 tech-savvy Gen Z consumers in Indonesia, who actively engage with AR features in e-commerce, we uncovered compelling insights into the dynamics at play. Our analysis, employing Structural Equation Modeling-Partial Least Squares (SEM-PLS), reveals that interactivity is not merely an enhancement but a catalyst, significantly influencing both mental imagery and consumer attitudes. Most strikingly, we find that consumer attitudes exert the strongest influence on digital behavioral intentions, highlighting their pivotal role in shaping purchase decisions and brand loyalty. This research underscores the urgency for businesses to elevate AR features—particularly interactivity and immersive experiences—if they wish to foster positive consumer perceptions and behaviors. The managerial takeaway is clear: invest in cutting-edge AR technologies and embed them into digital marketing strategies to not only captivate consumers but to also drive deeper engagement and satisfaction. While acknowledging limitations such as sample size and generalizability, this study lays the groundwork for future research to expand on these findings, exploring additional variables and diverse consumer segments. Keywords: Augmented Reality (AR); Digital Behavioral Intentions, Interactivity; Mental Image; Consumer Attitudes; E-commerce; Gen Z; Digital Marketing; Consumer Engagement